Preprocessing of Nepali News Corpus for Downstream Tasks - Awale, Sushil; Prasai, Suraj; Rijal, Birodh; Basnet, Santa B. (Nepalese Linguistics, 2022)
Text collected from online resources introduce a lot of errors which results in incorrect learning outcomes in automatic language learning tasks. In this paper, we discuss a Nepali text preprocessing pipeline to generate clean corpus. This pipeline is tested using a language model to observe impact of each steps in learning task. The relevancy of this work lies in systematizing the procedure in the development of standard Nepali corpus.